Legal Protection for Women and Children Victims of Domestic Violence in Gorontalo City - Latief, Vicky Chikita M.; Rusmulyadi, Rusmulyadi; Makkulawuzar, Kingdom (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2024)
Violence against women and children is worrying enough. There is a lot of violence against women and children in the domestic (household) environment. Violence against women and children is an act that is contrary to the basic principles of humanity. Because acts of violence against women are violations of human rights, a national legal instrument is needed to eliminate violence against women and children in Indonesia. The purpose of this research is to find out the legal protection efforts given to women and children as victims of domestic violence. data analysis The description used in this study is a qualitative type of qualitative research that aims to find facts, conditions, changes in phenomena, conditions during the research and what is presented. The results of this study indicate that there are efforts to protect themselves from the law. In Indonesian law, such as: Law Number 23 of 2004 concerning the Elimination of Domestic Violence Reform Forms of direct legal protection from existing institutions such as: Integrated service centers and legal support offices.